Peningkatan Pengetahuan Teknik Menyusui yang Benar “AMUBIDA” pada Ibu Menyusui di RS Puri Asih Salatiga - Shinta Lutfiani; Alya Fernanda Khairani; Heni Setyowati; Risma Aliviani Putri (Universitas Ngudi Waluyo, 2025)
Exclusive breastfeeding plays a vital role in supporting infant growth and stability. Infants who receive exclusive breastfeeding are 1.62 times more likely to grow normally compared to those who do not. In addition, exclusive breastfeeding supports the baby’s development in accordance with their age. Providing exclusive breastfeeding for up to six months contributes to achieving a child's optimal intellectual potential. According to data from the Basic Health Research (Riset Kesehatan Dasar), only 30.2% of infants in Indonesia receive exclusive breastfeeding until the age of six months. At Puri Asih Hospital in Salatiga, many breastfeeding mothers still lack knowledge about proper breastfeeding techniques, leading to delays in initiating breastfeeding for newborns and causing mothers to doubt themselves, often believing that their baby refuses to nurse. The instrument used in this study consisted of pre-test and post-test observation sheets. The method applied was a community service activity focusing on correct breastfeeding techniques using the